Teoria da mente: um procedimento de intervenção aplicado em crianças de 3 a 4 anos - Domingues, Simone Ferreira da Silva (2006)
There are evidences that the conversation and explanation about mind studies influence the capacity to comprehend one s mind which arises as the success in false belief tasks. However, there are still few studies about the theory of mind that may test the hypothesis of precedence concerning linguistic abilities related to the ability of assignment of mind states by applying intervention procedures. The experimental research presented herein is aimed at checking the effects of intervention over the assignment ability of children s mental states of belief. The investigation was done in three phases: pre-test, intervention and post-test. The intervention was based upon the explanation of false belief tasks followed by demonstrations using as aids gestures and objects aside from the explanatatory speech. Forty-four male and female children took part in this research. Their age vary from 3.5 to 4.7 years old and they attend a day care center for low income families in the east area of São Paulo. The attained results were possible through conversation with these children when they could talk about the events which involve mind actions, along with demonstrations and handling the material. Such results indicated that children from the experimental group (GE) partially benefited themselves from the interventional procedure, except in just one task, and it was observed a significant difference in the performance of the experimental group (GE) when compared to the performance of the control group (GC). The activities favored the occurrence of the attribution ability of mind states of belief and the effects remained in the experimental group (GE) after three weeks. The qualitative analysis concerning the behavior of the children from the experimental group during the playful situations applied as interventional procedure show a clear relation between implied participation and afterward advances in the false belief tasks. Therefore, under the intervention, when the children paid more attention and used more answers related to behavior explanations, they presented better results in the false belief tasks. On the other hand, children in whom intervention had no effect shared the lack of attention and did not give any answers related to behavior explanations. These results support the hypothesis pointing to the existence of a relation between the ability of assignment of mind states and the development of language. ABSTRACT There are evidences that the conversation and explanation about mind studies influence the capacity to comprehend one s mind which arises as the success in false belief tasks. However, there are still few studies about the theory of mind that may test the hypothesis of precedence concerning linguistic abilities related to the ability of assignment of mind states by applying intervention procedures. The experimental research presented herein is aimed at checking the effects of intervention over the assignment ability of children s mental states of belief. The investigation was done in three phases: pre-test, intervention and post-test. The intervention was based upon the explanation of false belief tasks followed by demonstrations using as aids gestures and objects aside from the explanatatory speech. Forty-four male and female children took part in this research. Their age vary from 3.5 to 4.7 years old and they attend a day care center for low income families in the east area of São Paulo. The attained results were possible through conversation with these children when they could talk about the events which involve mind actions, along with demonstrations and handling the material. Such results indicated that children from the experimental group (GE) partially benefited themselves from the interventional procedure, except in just one task, and it was observed a significant difference in the performance of the experimental group (GE) when compared to the performance of the control group (GC). The activities favored the occurrence of the attribution ability of mind states of belief and the effects remained in the experimental group (GE) after three weeks. The qualitative analysis concerning the behavior of the children from the experimental group during the playful situations applied as interventional procedure show a clear relation between implied participation and afterward advances in the false belief tasks. Therefore, under the intervention, when the children paid more attention and used more answers related to behavior explanations, they presented better results in the false belief tasks. On the other hand, children in whom intervention had no effect shared the lack of attention and did not give any answers related to behavior explanations. These results support the hypothesis pointing to the existence of a relation between the ability of assignment of mind states and the development of language